Autism Spectrum Disorder (ASD) and « Late Modernity » : What Correlations ? (London Journal of Research In Humanities and Social Sciences, 2025)
Is the increase in the number of subjects diagnosed with ASD related to the permanent revolution of late modernity as described by Harmut Rosa? The description of a particular phenotype of ASD in the study of Weill Cornell Medicine (2023) is an opportunity to test this hypothesis. By considering this phenotype of ASD as a complex sociological phenomenon and by applying a hologramic approach, we found in a phenomenological analysis of two clinical cases possible correlations: the difficulty of coping with the intensity of the presence-of-the-world perhaps due to sensoriality disorders, the need to carry out the program of the time despite everything through islands of competences.
Keywords: Phenomenology; ASD; late modernity; complex phenomenon